Pembinaan Apresiatif Mahasiswa PGSD Universitas Merangin dibidang Sastra Terapan tahun 2025 - Yusrizal, Yusrizal; Antoni, Wiko; Anwar, Khairul; Baitullah, Baitullah; Susilawati, Susilawati; Zamdani, Zamdani (PT. Meja Ilmiah Publikasi, 2025)
This activity aims to provide appreciative development for students of the Primary School Teacher Education (PGSD) Study Program at Universitas Merangin in the field of applied literature in 2025. Applied literature is understood as an educational tool that integrates literary values into learning contexts and character development. Through a practical approach, the development activities are carried out by both lecturers and students. The results of the activity show that appreciative development is implemented through various activities such as literary training, educational drama, and discussions on relevant contemporary literary works. This development not only enhances students’ appreciation of literature but also encourages their ability to adapt literary works into creative and contextual learning methods. These findings affirm the importance of integrating applied literature into the PGSD curriculum to shape future teachers who are humanistic, reflective, and innovative in their teaching.